A high friction coefficient organic rail brake pad material and preparation method thereof
By using organic rail brake pad materials with high friction coefficient, the problem of unstable friction coefficient in existing materials at high temperatures is solved, and a more efficient and safe braking effect is achieved during rail traffic braking.
Patent Information
- Application Number
- CN202411947669.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The friction coefficient of existing organic-based brake pad materials is unstable at high temperatures, which can easily lead to braking failure, increase operating costs, and affect the normal operation of rail transit.
Using an organic rail brake pad material with a high coefficient of friction, the formulation includes thermosetting phenolic resin, bismaleimide resin, polyimide resin, a variety of fibers and fillers, as well as specific additives and curing agents, the friction performance and stability of the material are improved through complex pretreatment, mixing and forming processes.
The material exhibits excellent friction performance, stability and wear resistance under high temperature and high pressure conditions, significantly improving the safety and efficiency of braking, reducing operating costs, and ensuring the normal operation of rail transit.
Smart Images

Figure CN119393472B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of brake pad materials, and in particular to an organic rail brake pad material with a high friction coefficient and a preparation method thereof. Background Art
[0002] With the rapid development of modern rail transit industry towards high speed and heavy load, the key role of the braking system in ensuring driving safety and operating efficiency has become increasingly prominent. As the core component of the braking system, the performance of brake pads directly determines the braking effect and the overall performance of the vehicle.
[0003] Metal-based brake pads have been used in the early rail transit braking field. Common materials include cast iron-based and copper-based materials. Cast iron-based brake pads have high hardness and certain wear resistance, which can meet the basic braking needs in low-speed and light-load rail vehicles. Copper-based brake pads have good thermal conductivity and have certain advantages in heat dissipation. However, metal-based brake pads have many difficult-to-overcome problems. On the one hand, their high density will increase the unsprung mass of the vehicle, which is extremely unfavorable for modern rail vehicles that pursue high-speed operation, because the large unsprung mass will affect the vehicle's dynamic performance, reduce ride comfort, and also increase track wear; on the other hand, the friction coefficient between metal-based brake pads and brake discs during braking is relatively low, and a large braking force is required to achieve effective braking, which not only increases the burden on the braking system, but also may cause excessive braking distance, endangering driving safety. In addition, the friction between metal and metal is prone to produce harsh noise and strong vibration, which will have adverse effects on the vehicle's mechanical structure and surrounding environment. Later, organic-based brake pads appeared. Traditional organic-based brake pads are mainly made of some general-purpose resins as the matrix, combined with a small amount of fiber and filler. For example, the early organic brake pads with phenolic resin as the main matrix can meet the braking requirements of some rail transit to a certain extent due to some characteristics of phenolic resin itself. Under normal temperature and medium and low speed braking conditions, this type of brake pad can work normally and realize the braking function of the vehicle. At the same time, organic-based brake pads have the advantage of light weight compared to metal-based brake pads, which is conducive to reducing the unsprung mass of the vehicle.
[0004] However, the existing organic-based brake pads still have room for further improvement in terms of high temperature resistance, friction coefficient, wear resistance, etc. The resin matrix of the existing organic-based brake pads is prone to thermal decomposition and aging at high temperatures, which damages the structure of the brake pads. For example, when the temperature exceeds a certain threshold, the traditional organic brake pads with a phenolic resin matrix will have obvious problems such as reduced hardness and unstable friction coefficient. In severe cases, the brakes may even fail, increasing the risk of driving safety. Frequent replacement of brake pads will not only increase operating costs, but also affect the normal operation of rail transit.
[0005] In view of this, the art needs an organic rail brake pad material with a high friction coefficient and a preparation method thereof to solve the above problems. Summary of the invention
[0006] In order to solve the above technical problems, that is, to solve the problems that the friction coefficient of existing organic-based brake pads is unstable, which leads to easy brake failure and thus affects driving safety, and frequent replacement of brake pads will increase operating costs and affect the normal operation of rail transit.
[0007] In one aspect, the present invention provides a high friction coefficient organic rail brake pad material, which includes, by mass percentage, 20-30% thermosetting phenolic resin, 8-15% bismaleimide resin, 8-12% polyimide resin, 6-10% high-strength carbon fiber, 6-10% aramid fiber, 4-8% basalt fiber, 3-6% graphite, 2-5% molybdenum disulfide, 3-6% copper fiber, 2-5% silicon carbide particles, 3-6% barium sulfate, 2-4% aluminum oxide, 2-4% talc, 2.5-5% curing agent and 1.5-3.5% other additives.
[0008] In certain preferred embodiments, the curing agent comprises: 1.5-3% hexamethylenetetramine and 1-2% dicumyl peroxide.
[0009] In certain preferred embodiments, the other additives include: 0.5-1.5% coupling agent, 0.5-1% lubricant and 0.5-1% antioxidant.
[0010] In certain preferred embodiments, the coupling agent includes at least one of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane and monoalkoxy titanate; the lubricant includes at least one of polyethylene wax, zinc stearate and polyethylene glycol; and the antioxidant includes at least one of hindered phenol antioxidants, phosphite antioxidants and butylated hydroxytoluene.
[0011] The high friction coefficient organic rail brake pad material of the present invention has the following beneficial effects:
[0012] The high friction coefficient organic rail brake pad material of the present invention shows excellent characteristics in terms of friction performance, effectively overcoming the shortcomings of existing brake pad materials in this regard. In the rail transit braking process, especially in response to complex conditions such as high temperature and high pressure generated by frequent braking under high-speed and heavy-load conditions, the material shows excellent performance. The resin matrix composed of thermosetting phenolic resin, bismaleimide resin and polyimide resin provides a stable structural basis for the entire material, ensuring that the material can still maintain good performance under high temperature environment, which creates conditions for the stable performance of friction performance. On this basis, the friction performance regulators cooperate with each other to greatly optimize the friction performance. The addition of graphite, with its excellent self-lubrication and good thermal conductivity, effectively reduces the fluctuation of the friction coefficient. During the braking process, it can form a lubricating film on the friction surface, making the friction between the pad and the brake disc more stable, avoiding the unstable braking force caused by the sudden change of the friction coefficient, which is very important for ensuring the safety and comfort of braking. The presence of molybdenum disulfide is It significantly reduces wear and enhances the stability of the material during the friction process. During braking, it can form a protective film on the surface of the friction pair to prevent direct contact and excessive wear between the materials, so that the brake pad can maintain stable friction performance during long-term use, effectively solving the problem of severe wear and decreased friction coefficient of traditional brake pads under frequent braking. Copper fiber not only enhances the thermal conductivity of the material, which is conducive to the rapid dissipation of heat and avoids the influence of local overheating on friction performance, but also improves the wear resistance of the material and increases the friction coefficient. This enables the brake pad to generate sufficient friction during the braking process to achieve efficient braking, greatly shorten the braking distance, and effectively address the problem of excessive braking distance in the prior art. Silicon carbide particles increase the hardness and wear resistance of the material by virtue of their high hardness, and further improve the friction performance. During the friction process, it can withstand greater pressure and friction, maintain the integrity of the material surface, and enable the brake pad to always maintain a stable friction coefficient under complex working conditions, avoiding the decrease in friction performance due to material wear.
[0013] On the other hand, the present invention also provides a method for preparing the above-mentioned high friction coefficient organic rail brake pad material, the preparation method comprising:
[0014] S1: pretreating the high-strength carbon fiber, the aramid fiber, the basalt fiber, the barium sulfate, the aluminum oxide and the talc;
[0015] S2: adding the thermosetting phenolic resin, the bismaleimide resin and the polyimide resin into a reaction kettle in proportion, heating and stirring, and then sequentially adding a coupling agent, a curing agent and an antioxidant into the reaction kettle and continuing stirring;
[0016] S3: adding the pretreated barium sulfate, aluminum oxide, talcum powder, graphite, molybdenum disulfide, copper fiber, and silicon carbide particles into a high-speed mixer in proportion, heating and stirring, and adding a lubricant during the stirring and mixing process;
[0017] S4: adding the mixed powder into a reactor and stirring, and then adding the pretreated high-strength carbon fiber, the aramid fiber, and the basalt fiber into the mixed liquid in the reactor and stirring;
[0018] S5: pouring the mixed material stirred in step S4 into a mold and molding it by injection molding;
[0019] S6: taking the formed product out of the mold and putting it into an oven for curing;
[0020] S7: Perform mechanical processing, surface treatment and heat treatment on the cured product.
[0021] In some preferred embodiments, step S1 specifically includes:
[0022] S11: soaking the high-strength carbon fiber in nitric acid or potassium permanganate solution for 3-5 hours at a temperature of 50-70° C., then rinsing the high-strength carbon fiber with deionized water, and then drying the high-strength carbon fiber at 80-100° C. for 4-6 hours;
[0023] S12: impregnating the aramid fiber with a mixed solution of a silane coupling agent and a titanate coupling agent in a mass ratio of 1:1 for 2-4 hours at a temperature of 60-80° C., then rinsing the aramid fiber with deionized water, and drying the aramid fiber at 100-120° C. for 3-5 hours;
[0024] S13: using a plasma treatment device to perform surface plasma treatment on the basalt fiber, the treatment time is 1-2 hours, and the power is 500-1000W;
[0025] S14: drying the barium sulfate, the aluminum oxide and the talc powder respectively at a drying temperature of 120-150° C. for 5-8 hours, and then grinding the barium sulfate, the aluminum oxide and the talc powder respectively to make the particle sizes of the barium sulfate, the aluminum oxide and the talc powder be 1-5 μm.
[0026] In some preferred embodiments, step S2 specifically includes:
[0027] S21: adding the thermosetting phenolic resin into a reaction kettle, and stirring at 90-110° C. for 0.5 hour;
[0028] S22: Add the bismaleimide resin into the reaction kettle and continue stirring for 0.5 hours;
[0029] S23: Add the polyimide resin into the reaction kettle and continue stirring for 0.5 hours;
[0030] S24: Add coupling agent to the reaction kettle and maintain the temperature at 90-110° C., and continue stirring for a total of 1.5-2.5 hours;
[0031] S25: adding hexamethylenetetramine to the reaction kettle and continuing stirring for 0.25-0.5 hours;
[0032] S26: Add dicumyl peroxide to the reactor and continue stirring for 0.25-0.5 hours;
[0033] S27: Add antioxidant to the reactor and continue stirring for 0.3-0.5 hours.
[0034] In certain preferred embodiments, in step S3, the heating temperature of the high-speed mixer is 60-80° C., and the stirring and mixing time is 1.5-2.5 hours; and / or,
[0035] In step S4, the mixed powder is added to a reactor and stirred for 0.5 hours, and the pretreated high-strength carbon fiber, the aramid fiber, and the basalt fiber are added to the mixed liquid in the reactor and stirred. Ultrasonic dispersion is performed during stirring. The stirring time is 2.5-3.5 hours, and the ultrasonic power is 800-1200W.
[0036] In certain preferred embodiments, during the injection molding process of step S5, a magnetic field with a strength of 0.5-1T is applied to the mold by a magnetic field generating device; and / or,
[0037] In step S5, the injection molding temperature is 190-210°C and the pressure is 60-90 MPa.
[0038] In certain preferred embodiments, in step S6, the oven gradually raises the temperature from room temperature to 190-210° C. at a heating rate of 2-3° C. / min, and the curing time is 5-7 hours; and / or,
[0039] During the curing process of the product, ultraviolet light is used to irradiate the surface of the product. The wavelength of ultraviolet light is 200-400nm and the irradiation intensity is 10-20mW / cm².
[0040] The preparation method of the high friction coefficient organic rail brake pad material of the present invention has the following beneficial effects:
[0041] The present invention improves the bonding force and compatibility of the fiber and the resin by special treatment of the fiber, so that the fiber can better play a reinforcing role in the material, ensure the stability of the material structure during the friction process, and thus provide strong support for stable friction performance. The pretreatment of the filler, such as controlling the particle size of barium sulfate, aluminum oxide and talcum powder and removing impurities, can make them more evenly distributed in the material, ensure the flatness and consistency of the material surface during the friction process, and avoid local friction performance differences caused by uneven distribution of fillers. In the mixing and adding steps, the thermosetting phenolic resin, bismaleimide resin and polyimide resin are first heated and stirred in a reaction kettle to prepare the subsequent components. The uniform dispersion creates a good environment, and then the coupling agent, curing agent and antioxidant are added in turn. The coupling agent strengthens the combination of fiber and resin, the curing agent ensures the curing effect of the material, and the antioxidant prevents the material from being degraded due to oxidation during use. These indirectly guarantee the stability of friction performance. In the powder mixing stage, the pretreated barium sulfate, aluminum oxide, talcum powder, graphite, molybdenum disulfide, copper fiber, and silicon carbide particles are heated and stirred in a high-speed mixer, and lubricant is added. This method can fully mix various friction performance regulators and fillers to ensure that they are evenly distributed in the material, so that they can work together when the brake pad is used, effectively improving the friction Performance, the addition of lubricants can also reduce the friction of materials during the preparation process, and avoid the original friction performance setting of the material being affected by improper operations during the preparation process. Injection molding also plays an important role in improving friction performance. This molding method can accurately control the shape and size of the brake pad, ensuring good contact between the brake pad and the brake disc, making the friction surface more fitted, thereby improving friction efficiency. At the same time, injection molding can make the material fill the mold quickly and evenly, avoiding defects such as pores and cracks inside the material, ensuring the uniformity of the material's density, so that during the braking process, the friction performance of the brake pad is consistent everywhere, avoiding friction caused by local defects. Unstable phenomenon, the final post-processing step further optimizes the friction performance, mechanical processing makes the product reach precise size and shape, ensures the matching accuracy between the brake pad and the brake disc, and thus guarantees a stable friction effect, surface treatment significantly improves the surface quality and wear resistance of the product, the wear-resistant coating can form an extra protective film on the friction surface, further reduce wear, maintain a stable friction coefficient, polishing makes the friction surface smoother, reduces unnecessary friction resistance, the heat treatment step eliminates the residual stress inside the product, improves the performance stability of the material, and ensures that the friction performance of the brake pad under complex working conditions is not affected by internal stress changes and always remains in the best state.Through the synergistic effect of this series of preparation methods, the friction performance of the prepared high-friction coefficient organic rail brake pad material has been greatly improved, effectively solving the shortcomings of existing brake pad materials in friction performance and providing reliable guarantee for the high-performance operation of rail transit braking systems. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] The features and advantages of the present invention will be more clearly understood by referring to the accompanying drawings, which are schematic and should not be construed as limiting the present invention in any way. In the accompanying drawings:
[0043] Figure 1 The present invention is a flow chart of the method for preparing the high friction coefficient organic rail brake pad material. DETAILED DESCRIPTION
[0044] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0045] Based on the problems pointed out in the background technology that the friction coefficient of existing organic-based brake pads is unstable, which leads to easy brake failure and thus affects driving safety, and frequent replacement of brake pads will increase operating costs and affect the normal operation of rail transit, the present invention provides a high friction coefficient organic rail brake pad material and a preparation method thereof, aiming to improve its friction performance without reducing other properties of the organic rail brake pad material, effectively solve the shortcomings of existing brake pad materials in terms of friction performance, and provide reliable guarantee for the high-performance and safe operation of rail transit.
[0046] The high friction coefficient organic rail brake pad material of the present invention comprises: measured by mass percentage: 20-30% of thermosetting phenolic resin, 8-15% of bismaleimide resin, 8-12% of polyimide resin, 6-10% of high-strength carbon fiber, 6-10% of aramid fiber, 4-8% of basalt fiber, 3-6% of graphite, 2-5% of molybdenum disulfide, 3-6% of copper fiber, 2-5% of silicon carbide particles, 3-6% of barium sulfate, 2-4% of aluminum oxide, 2-4% of talc powder, 2.5-5% of curing agent and 1.5-3.5% of other additives.
[0047] In the above, the high-strength carbon fiber of the present invention refers to carbon fiber with a tensile strength exceeding 5000MPa. Thermosetting phenolic resin is a resin generated by the reaction of phenols and aldehydes under the action of an alkaline catalyst. It contains active groups that can further react. After heating or adding a curing agent, it can undergo a cross-linking reaction to form a three-dimensional network of highly cross-linked body structures. Once cured, it can no longer melt or dissolve, and has good thermal stability, mechanical strength and chemical corrosion resistance.
[0048] Preferably, the curing agent includes: 1.5-3% hexamethylenetetramine and 1-2% dicumyl peroxide; other additives include: 0.5-1.5% coupling agent, 0.5-1% lubricant and 0.5-1% antioxidant.
[0049] In the above, the coupling agent includes at least one of γ-aminopropyltriethoxysilane (KH-550), γ-glycidyloxypropyltrimethoxysilane (KH-560) and monoalkoxy titanate (NDZ-101); the lubricant includes at least one of polyethylene wax (LicowaxE), zinc stearate and polyethylene glycol (PEG); the antioxidant includes at least one of hindered phenol antioxidants, phosphite antioxidants and butylated hydroxytoluene, the hindered phenol antioxidant is preferably Irganox1010, the chemical name of which is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, the phosphite antioxidant is preferably antioxidant 168, the chemical name of which is tris(2,4-di-tert-butylphenyl) phosphite, and the chemical name of butylated hydroxytoluene (BHT) is 2,6-di-tert-butyl-4-methylphenol.
[0050] In the high friction coefficient organic rail brake pad material of the present invention, the molecular chains of the thermosetting phenolic resin form a basic heat-resistant skeleton through cross-linking, and the active groups in the molecular structure of the bismaleimide resin interact with the phenolic resin to further strengthen the skeleton structure and increase the cross-linking density, making it more difficult for the molecular chains of the material to move and decompose at high temperatures. The polyimide resin is evenly dispersed in this system, and its own heat-resistant structure cooperates with the other two resins to form a highly stable heat-resistant network at the microscopic level, so that the material can effectively avoid softening and decomposition of the resin matrix under the high temperature environment generated by rail transit braking, maintain the overall stability of the material, and far surpass the existing organic-based brake pads that are prone to failure at high temperatures. Limitations; coupling agents (γ-aminopropyl triethoxysilane (KH-550), γ-glycidyloxypropyl trimethoxysilane (KH-560) and monoalkoxy titanate (NDZ-101)) form strong chemical bonds between the fiber surface and the resin matrix. These chemical bonds are like countless tiny "anchor points" that firmly fix the fiber in the resin. At the same time, at the microscopic level, the high modulus and high strength characteristics of carbon fiber provide a mechanical support skeleton for the material. Its good thermal conductivity can quickly conduct heat along the fiber direction to form a microscopic heat conduction channel; the molecular chain structure of aramid fiber gives it excellent toughness. When it is impacted and rubbed, it can absorb energy through the stretching and deformation of the molecular chain to prevent cracks in the material. The basalt fiber, with its unique mineral composition and microstructure, enhances the material's tolerance to high temperature and corrosive environments. The synergistic reinforcement of multiple fibers at the micro level and the strong combination with the resin effectively overcome the problems of poor fiber reinforcement and easy separation from the matrix in the existing technology, greatly improving the mechanical properties and wear resistance of the material. Graphite, molybdenum disulfide, copper fiber and silicon carbide particles form a mutually coordinated friction optimization system in the microstructure. Graphite has a typical layered microstructure. During the friction process, these layered structures can slide relative to each other to form a lubricating film, thereby reducing the fluctuation of the friction coefficient. The microscopic hexagonal structure of molybdenum disulfide enables it to form a low shear strength protective film on the friction surface, which is compatible with the graphite. The lubrication effects complement each other and further stabilize the friction coefficient. Copper fiber not only serves as a channel to enhance heat conduction at the micro level, but its metal properties can produce a synergistic effect with other regulators during the friction process, increasing the actual contact area and friction between the friction pairs, while improving the wear resistance of the material. Silicon carbide particles, with their high-hardness microscopic crystal structure, protrude on the friction surface, increase the microscopic roughness of the material, increase the friction coefficient, and can withstand greater pressure during the friction process to prevent excessive wear of the material. The synergistic effect of these four friction performance regulators at the micro level can enable the brake pad to maintain a high and stable friction coefficient under various working conditions, effectively solving the problem of unstable friction coefficient and severe wear of existing brake pads.The high-density microstructure of barium sulfate increases the overall density of the material and provides stable support during the friction process. At the same time, its uniform distribution in the material helps to improve the hardness of the material. The high-hardness microcrystalline structure of aluminum oxide can enhance the wear resistance of the material, and its stability at high temperatures helps to maintain the performance of the material under high-temperature conditions. The layered microstructure of talcum powder has a certain lubricity, which can improve the fluidity of the material during material processing and help reduce the fluctuation of the friction coefficient during use. There are microscopic interactions between these fillers and fibers, resins and friction performance modifiers. For example, fillers can be filled in the tiny gaps between fibers and resins to further improve the density of the material. At the same time, they work synergistically with friction performance modifiers to optimize the friction and wear resistance of the material, overcoming the shortcomings of the prior art that fillers are only used as simple filling components and fail to give full play to their comprehensive performance. Hexamethylenetetramine can form stable crosslinking points between resin molecules, and diisopropylbenzene peroxide can accelerate the crosslinking reaction. The two work together to quickly and fully solidify the resin to form a stable three-dimensional network structure. The antioxidant (Irganox 1010, antioxidant 168 and butylated hydroxytoluene (BHT) play a role in capturing free radicals at the microscopic level. During the use of brake pads, especially in the complex environment of high temperature and friction, the material is prone to generate free radicals. Antioxidants can capture these free radicals in time, inhibit the chain propagation of oxidation reactions, and prevent the resin matrix from oxidative degradation at the microscopic level, thereby ensuring the long-term stability of the material. The synergistic effect of this curing agent and antioxidant effectively solves the problem of performance degradation of existing brake pad materials due to incomplete curing or oxidative aging during long-term use. ;
[0051] like Figure 1 As shown, the preparation method of the high friction coefficient organic rail brake pad material of the present invention comprises:
[0052] S1: Pretreatment of high-strength carbon fiber, aramid fiber, basalt fiber, barium sulfate, alumina and talc;
[0053] In a preferred embodiment, the above step S1 specifically includes:
[0054] S11: soaking the high-strength carbon fiber in nitric acid or potassium permanganate solution for 3-5 hours at a temperature of 50-70°C, then rinsing the high-strength carbon fiber with deionized water, and then drying the high-strength carbon fiber at 80-100°C for 4-6 hours; further preferably, the dried carbon fiber may be coated with carbon nanotubes, specifically, a layer of carbon nanotubes is uniformly coated on the surface of the carbon fiber by chemical vapor deposition, and the content of the carbon nanotubes is controlled to be 1%-3% of the mass of the high-strength carbon fiber. This treatment can further enhance the strength and thermal conductivity of the carbon fiber, and at the same time provide more binding sites between the fiber and the resin, thereby improving the overall performance of the material;
[0055] S12: The aramid fiber is impregnated with a mixed solution of a silane coupling agent and a titanate coupling agent in a mass ratio of 1:1 for 2-4 hours at a temperature of 60-80°C, and then the aramid fiber is rinsed with deionized water and dried at 100-120°C for 3-5 hours; further preferably, the aramid fiber after the silanization treatment is subjected to ion implantation, the implanted ions are nitrogen ions or titanium ions, the implantation energy is 30-50keV, and the dosage is 1×10¹ 5 -1×10¹ 6 ions / cm², ion implantation can change the chemical composition and physical structure of the aramid fiber surface, increase the fiber surface activity, thereby better combining with the resin, and at the same time improve the fiber's own wear resistance;
[0056] S13: performing surface plasma treatment on the basalt fiber using a plasma treatment device, the treatment time is 1-2 hours, and the power is 500-1000W; further preferably, performing rare earth element doping treatment on the basalt fiber after the plasma treatment, soaking the basalt fiber in a solution containing rare earth elements (such as lanthanum, cerium, etc.) for 6-8 hours, and then drying at 120-150°C. Rare earth element doping can improve the high temperature resistance and oxidation resistance of the basalt fiber, and enhance the stability of the fiber in a high temperature environment;
[0057] S14: Drying the barium sulfate, aluminum oxide and talc powder respectively at a drying temperature of 120-150° C. for 5-8 hours, and then grinding the barium sulfate, aluminum oxide and talc powder respectively to make the particle sizes of the barium sulfate, aluminum oxide and talc powder be 1-5 μm.
[0058] S2: adding thermosetting phenolic resin, bismaleimide resin and polyimide resin into a reaction kettle in proportion, heating and stirring, and then adding coupling agent, curing agent and antioxidant into the reaction kettle in sequence and continuing to stir;
[0059] In a preferred embodiment, the above step S2 specifically includes:
[0060] S21: adding a thermosetting phenolic resin into a reaction kettle and stirring at 90-110° C. for 0.5 hour;
[0061] S22: Add bismaleimide resin to the reactor and continue stirring for 0.5 hours;
[0062] S23: Add polyimide resin into the reaction kettle and continue stirring for 0.5 hours;
[0063] S24: Add coupling agent to the reaction kettle and maintain the temperature at 90-110° C., and continue stirring for a total of 1.5-2.5 hours;
[0064] S25: adding hexamethylenetetramine to the reaction kettle and continuing stirring for 0.25-0.5 hours;
[0065] S26: Add dicumyl peroxide to the reactor and continue stirring for 0.25-0.5 hours;
[0066] S27: Add antioxidant to the reactor and continue stirring for 0.3-0.5 hours.
[0067] Further preferably, in the process of mixing and stirring the above three resins, graphene quantum dots accounting for 0.5-1% of the total mass of the resin are added. Graphene quantum dots have excellent thermal conductivity and mechanical properties and can effectively enhance the comprehensive properties of the resin matrix.
[0068] S3: adding the pretreated barium sulfate, aluminum oxide, talcum powder, graphite, molybdenum disulfide, copper fiber, and silicon carbide particles into a high-speed mixer in proportion, heating and stirring, and adding a lubricant during the stirring and mixing process;
[0069] In a preferred embodiment, the heating temperature of the high-speed mixer is 60-80°C, and the stirring and mixing time is 1.5-2.5 hours; further, in the powder mixing stage, 0.2-0.5% of the total mass of the powder is added with nano-titanium dioxide. Nano-titanium dioxide can improve the hardness and wear resistance of the material, and at the same time improve the high temperature resistance of the material to a certain extent, which helps to improve the performance of the brake pad under complex working conditions.
[0070] S4: adding the mixed powder into a reactor and stirring, and then adding the pretreated high-strength carbon fiber, aramid fiber, and basalt fiber into the mixed liquid in the reactor and stirring;
[0071] In a preferred embodiment, in the above step S4, the mixed powder is added to the reactor and stirred for 0.5 hour, and the pretreated high-strength carbon fiber, aramid fiber, and basalt fiber are added to the mixed liquid in the reactor and stirred, and ultrasonic dispersion is performed during stirring. The stirring time is 2.5-3.5 hours and the ultrasonic power is 800-1200W; further preferably, in the process of adding high-strength carbon fiber, aramid fiber, and basalt fiber, polydopamine nanoparticles accounting for 0.3-0.6% of the total mass of the fiber are added at the same time. The polydopamine nanoparticles can form a coating with good adhesion and biocompatibility on the fiber surface, further enhancing the bonding force between the fiber and the resin, and improving the overall toughness and wear resistance of the material.
[0072] S5: pouring the mixed material stirred in step S4 into a mold and molding it by injection molding;
[0073] In a preferred embodiment, during the injection molding process of the above step S5, a magnetic field with a strength of 0.5-1T is applied to the mold by a magnetic field generating device. The magnetic field can orient the copper fibers in the material and improve the performance of the material in a specific direction, such as thermal conductivity and friction performance. The injection molding temperature is 190-210°C and the pressure is 60-90MPa.
[0074] S6: taking the formed product out of the mold and putting it into an oven for curing;
[0075] In a preferred embodiment, in the above step S6, the oven gradually increases the temperature from room temperature to 190-210°C at a heating rate of 2-3°C / min, and the curing time is 5-7 hours. During the curing process of the product, the surface of the product is irradiated with ultraviolet light, the wavelength of the ultraviolet light is 200-400nm, and the irradiation intensity is 10-20mW / cm². The ultraviolet light irradiation further promotes the cross-linking and curing of the resin and improves the hardness and wear resistance of the surface of the product.
[0076] S7: Mechanical processing, surface treatment and heat treatment of the cured product;
[0077] In the above step S7, the surface treatment is performed on the machined product, such as spraying a wear-resistant coating, polishing, etc., to improve the surface quality and wear resistance of the product. Specifically, wear-resistant materials such as polytetrafluoroethylene coating or tungsten carbide coating can be used for spraying treatment. Before spraying the wear-resistant coating, the surface of the product is firstly subjected to plasma etching treatment, and the etching power is 300-500W, and the time is 10-20 minutes. Plasma etching can increase the roughness of the surface of the product and improve the adhesion between the coating and the product. The heat treatment temperature is 150-180°C, and the time is 2-4 hours. During the heat treatment process, the product is placed in an atmosphere containing a mixed gas of nitrogen and hydrogen (volume ratio is 9:1). This mixed gas atmosphere can prevent the product from oxidizing during the heat treatment process. At the same time, hydrogen can react with some active oxygen groups that may exist inside the material to further improve the material's antioxidant properties.
[0078] The technical solution of the present invention is further described below in conjunction with a plurality of embodiments and comparative examples.
[0079] Example 1
[0080] High friction coefficient organic rail brake pad materials measured by mass percentage include:
[0081] Thermosetting phenolic resin 23%, bismaleimide resin 10%, polyimide resin 10%, high-strength carbon fiber 10%, aramid fiber 10%, basalt fiber 8%, graphite 4%, molybdenum disulfide 3%, copper fiber 4%, silicon carbide particles 3%, barium sulfate 4%, aluminum oxide 3%, talc 3%, hexamethylenetetramine 1.5%, diisopropyl peroxide 1.5%, γ-aminopropyl triethoxysilane (coupling agent) 1%, polyethylene wax (lubricant) 0.5%, Irganox 1010 (antioxidant) 0.5%;
[0082] The method for preparing the high friction coefficient organic rail brake pad material comprises:
[0083] The high-strength carbon fiber was immersed in a nitric acid solution for 4 hours at a temperature of 60°C, and then the high-strength carbon fiber was rinsed with deionized water and dried at 90°C for 5 hours; the aramid fiber was impregnated with a mixed solution of a silane coupling agent and a titanate coupling agent in a mass ratio of 1:1 for 3 hours at a temperature of 70°C, and then the aramid fiber was rinsed with deionized water and dried at 110°C for 4 hours; the basalt fiber was surface plasma treated with a plasma treatment device for 1.5 hours at a power of 800W; barium sulfate, aluminum oxide and talc were dried at a temperature of 130°C for 6 hours, and then the barium sulfate, aluminum oxide and talc were ground to make the particle size of barium sulfate, aluminum oxide and talc 3μm;
[0084] Add thermosetting phenolic resin to the reactor and stir at 100°C for 0.5 hours; add bismaleimide resin to the reactor and continue stirring for 0.5 hours; add polyimide resin to the reactor and continue stirring for 0.5 hours; add coupling agent to the reactor and keep the temperature at 100°C, and continue stirring for 2 hours; add hexamethylenetetramine to the reactor and continue stirring for 0.3 hours; add diisopropylbenzene peroxide to the reactor and continue stirring for 0.3 hours; add antioxidant to the reactor and continue stirring for 0.4 hours;
[0085] The pretreated barium sulfate, aluminum oxide, talcum powder, graphite, molybdenum disulfide, copper fiber, and silicon carbide particles are added to a high-speed mixer in proportion for heating and stirring. The heating temperature of the high-speed mixer is 70° C. The stirring and mixing time is 2 hours. A lubricant is added during the stirring and mixing process.
[0086] The mixed powder was added into the reactor and stirred for 0.5 hours, and then the pretreated high-strength carbon fiber, aramid fiber and basalt fiber were added into the mixed solution in the reactor and stirred, and ultrasonic dispersion was performed during stirring. The stirring time was 3 hours and the ultrasonic power was 1000W.
[0087] The stirred mixed material is poured into a mold and molded by injection molding. A magnetic field with a strength of 0.8T is applied to the mold by a magnetic field generating device. The injection molding temperature is 200°C and the pressure is 70MPa.
[0088] The formed product is taken out of the mold and placed in an oven for curing. The temperature is gradually increased from room temperature to 200°C at a heating rate of 2.5°C / min. The curing time is 6 hours. During the curing process, the surface of the product is irradiated with ultraviolet light with a wavelength of 300nm and an irradiation intensity of 15mW / cm².
[0089] Example 2
[0090] The high friction coefficient organic track brake pad material is the same as in Example 1;
[0091] The method for preparing the high friction coefficient organic rail brake pad material comprises:
[0092] The high-strength carbon fiber was soaked in potassium permanganate solution for 3 hours at a temperature of 50°C, and then the high-strength carbon fiber was rinsed with deionized water and then dried at 80°C for 4 hours; the aramid fiber treatment, basalt fiber treatment, filler treatment, resin mixing, and powder mixing were the same as in Example 1;
[0093] The mixed powder was added into the reactor and stirred for 0.5 hours, and then the pretreated high-strength carbon fiber, aramid fiber and basalt fiber were added into the mixed solution in the reactor and stirred, and ultrasonic dispersion was used during stirring. The stirring time was 2.5 hours and the ultrasonic power was 800W.
[0094] The stirred mixed material is poured into a mold and molded by injection molding. A magnetic field with a strength of 0.5T is applied to the mold by a magnetic field generating device. The temperature of injection molding is 190°C and the pressure is 60MPa.
[0095] The formed product is taken out of the mold and placed in an oven for curing. The temperature is gradually increased from room temperature to 190°C at a heating rate of 2°C / min. The curing time is 5 hours. During the curing process, the surface of the product is irradiated with ultraviolet light with a wavelength of 200nm and an irradiation intensity of 10mW / cm².
[0096] Example 3
[0097] The high friction coefficient organic track brake pad material is the same as in Example 1;
[0098] The method for preparing the high friction coefficient organic rail brake pad material comprises:
[0099] The high-strength carbon fiber was soaked in a nitric acid solution for 5 hours at a temperature of 70°C, and then the high-strength carbon fiber was rinsed with deionized water, and then dried at 100°C for 6 hours; the aramid fiber treatment, basalt fiber treatment, filler treatment, resin mixing, and powder mixing were the same as in Example 1;
[0100] The mixed powder was added into the reactor and stirred for 0.5 hours, and then the pretreated high-strength carbon fiber, aramid fiber and basalt fiber were added into the mixed solution in the reactor and stirred, and ultrasonic dispersion was used during stirring. The stirring time was 3.5 hours and the ultrasonic power was 1200W.
[0101] The stirred mixed material is poured into a mold and molded by injection molding. A magnetic field with a strength of 1T is applied to the mold by a magnetic field generating device. The temperature of injection molding is 210°C and the pressure is 90MPa.
[0102] The formed product is taken out of the mold and placed in an oven for curing. The temperature is gradually increased from room temperature to 210°C at a heating rate of 3°C / min. The curing time is 7 hours. During the curing process, the surface of the product is irradiated with ultraviolet light with a wavelength of 400nm and an irradiation intensity of 20mW / cm².
[0103] Example 4
[0104] High friction coefficient organic rail brake pad materials measured by mass percentage include:
[0105] Thermosetting phenolic resin 26%, bismaleimide resin 13%, polyimide resin 10%, high-strength carbon fiber 10%, aramid fiber 10%, basalt fiber 8%, graphite 4%, molybdenum disulfide 3%, copper fiber 4%, silicon carbide particles 3%, barium sulfate 4%, aluminum oxide 3%, talc 3%, hexamethylenetetramine 1.5%, diisopropylbenzene peroxide 1.5%, γ-glycidyloxypropyltrimethoxysilane (coupling agent) 1%, zinc stearate (lubricant) 0.5%, antioxidant 168 (antioxidant) 0.5%;
[0106] The method for preparing the high friction coefficient organic rail brake pad material comprises:
[0107] 1. The high-strength carbon fiber was immersed in a nitric acid solution for 3.5 hours at a temperature of 55°C, and then the high-strength carbon fiber was rinsed with deionized water and dried at 85°C for 4.5 hours; 2. Aramid fiber treatment: A mixed solution of a silane coupling agent and a titanate coupling agent with a mass ratio of 1:1 was used to immerse the aramid fiber for 2 hours at a temperature of 60°C, and then the aramid fiber was rinsed with deionized water and dried at 100°C for 3 hours; Surface plasma treatment of basalt fiber was performed using plasma treatment equipment for 1 hour at a power of 500W; barium sulfate, aluminum oxide and talcum powder were dried separately at a drying temperature of 120°C for 5 hours, and then barium sulfate, aluminum oxide and talcum powder were ground separately to make the particle size of barium sulfate, aluminum oxide and talcum powder 1μm;
[0108] Add thermosetting phenolic resin to the reactor and stir at 90°C for 0.5 hour; add bismaleimide resin to the reactor and continue stirring for 0.5 hour; add polyimide resin to the reactor and continue stirring for 0.5 hour; add coupling agent to the reactor and keep the temperature at 90°C, and continue stirring for a total of 1.5 hours; add hexamethylenetetramine to the reactor and continue stirring for 0.25 hour; add diisopropylbenzene peroxide to the reactor and continue stirring for 0.25 hour; add antioxidant to the reactor and continue stirring for 0.3 hour;
[0109] The pretreated barium sulfate, aluminum oxide, talcum powder, graphite, molybdenum disulfide, copper fiber, and silicon carbide particles are added to a high-speed mixer in proportion for heating and stirring. The heating temperature of the high-speed mixer is 60° C. The stirring and mixing time is 1.5 hours. A lubricant is added during the stirring and mixing process.
[0110] The mixed powder was added into the reactor and stirred for 0.5 hours, and then the pretreated high-strength carbon fiber, aramid fiber and basalt fiber were added into the mixed solution in the reactor and stirred, and ultrasonic dispersion was used during stirring. The stirring time was 2.5 hours and the ultrasonic power was 900W.
[0111] The stirred mixed material is poured into a mold and molded by injection molding. A magnetic field with a strength of 0.6T is applied to the mold by a magnetic field generating device. The injection molding temperature is 195°C and the pressure is 75MPa.
[0112] The formed product is taken out of the mold and placed in an oven for curing. The temperature is gradually raised from room temperature to 195°C at a heating rate of 2.2°C / min. The curing time is 5.5 hours. During the curing process, the surface of the product is irradiated with ultraviolet light with a wavelength of 250nm and an irradiation intensity of 12mW / cm².
[0113] Example 5
[0114] The high friction coefficient organic track brake pad material is the same as that of Example 4;
[0115] The method for preparing the high friction coefficient organic rail brake pad material comprises:
[0116] The high-strength carbon fiber was soaked in potassium permanganate solution for 4.5 hours at a temperature of 65°C, and then the high-strength carbon fiber was rinsed with deionized water and then dried at 95°C for 5.5 hours; the aramid fiber treatment, basalt fiber treatment, filler treatment, resin mixing, and powder mixing were the same as in Example 4;
[0117] The mixed powder was added into the reactor and stirred for 0.5 hours, and then the pretreated high-strength carbon fiber, aramid fiber and basalt fiber were added into the mixed solution in the reactor and stirred, and ultrasonic dispersion was performed during stirring. The stirring time was 3.2 hours and the ultrasonic power was 1100W.
[0118] The stirred mixed material is poured into a mold and molded by injection molding. A magnetic field with a strength of 0.9T is applied to the mold by a magnetic field generating device. The temperature of injection molding is 205°C and the pressure is 85MPa.
[0119] The formed product is taken out of the mold and placed in an oven for curing. The temperature is gradually increased from room temperature to 205°C at a heating rate of 2.8°C / min. The curing time is 6.5 hours. During the curing process, the surface of the product is irradiated with ultraviolet light with a wavelength of 350nm and an irradiation intensity of 18mW / cm².
[0120] Example 6
[0121] The high friction coefficient organic track brake pad material is the same as that of Example 4;
[0122] The method for preparing the high friction coefficient organic rail brake pad material comprises:
[0123] The high-strength carbon fiber was soaked in a nitric acid solution for 4 hours at a temperature of 60°C, and then the high-strength carbon fiber was rinsed with deionized water and then dried at 90°C for 5 hours; the aramid fiber treatment, basalt fiber treatment, filler treatment, resin mixing, and powder mixing were the same as in Example 4;
[0124] The mixed powder was added into the reactor and stirred for 0.5 hours, and then the pretreated high-strength carbon fiber, aramid fiber and basalt fiber were added into the mixed solution in the reactor and stirred, and ultrasonic dispersion was performed during stirring. The stirring time was 3 hours and the ultrasonic power was 1000W.
[0125] The stirred mixed material is poured into a mold and molded by injection molding. A magnetic field with a strength of 0.7T is applied to the mold by a magnetic field generating device. The injection molding temperature is 200°C and the pressure is 80MPa.
[0126] The formed product is taken out of the mold and placed in an oven for curing. The temperature is gradually increased from room temperature to 200°C at a heating rate of 2.5°C / min. The curing time is 6 hours. During the curing process, the surface of the product is irradiated with ultraviolet light with a wavelength of 300nm and an irradiation intensity of 15mW / cm².
[0127] Example 7
[0128] High friction coefficient organic rail brake pad materials measured by mass percentage include:
[0129] Thermosetting phenolic resin 30%, bismaleimide resin 15%, polyimide resin 10%, high-strength carbon fiber 6%, aramid fiber 6%, basalt fiber 4%, graphite 4%, molybdenum disulfide 3%, copper fiber 4%, silicon carbide particles 3%, barium sulfate 4%, aluminum oxide 3%, talc 3%, hexamethylenetetramine 1.5%, diisopropylbenzene peroxide 1.5%, monoalkoxy titanate (coupling agent) 1%, polyethylene glycol (lubricant) 0.5%, BHT (antioxidant) 0.5%;
[0130] The method for preparing the high friction coefficient organic rail brake pad material comprises:
[0131] The high-strength carbon fiber was immersed in a nitric acid solution for 4.5 hours at a temperature of 65°C, and then the high-strength carbon fiber was rinsed with deionized water and dried at 95°C for 5.5 hours; the aramid fiber was impregnated with a mixed solution of a silane coupling agent and a titanate coupling agent in a mass ratio of 1:1 for 3.5 hours at a temperature of 75°C, and then the aramid fiber was rinsed with deionized water and dried at 115°C for 4.5 hours; the basalt fiber was surface plasma treated with a plasma treatment device for 2 hours at a power of 1000W; barium sulfate, aluminum oxide and talc were dried at a temperature of 150°C for 8 hours, and then the barium sulfate, aluminum oxide and talc were ground to make the particle size of barium sulfate, aluminum oxide and talc 5μm;
[0132] Add thermosetting phenolic resin to the reactor and stir at 110°C for 0.5 hour; add bismaleimide resin to the reactor and continue stirring for 0.5 hour; add polyimide resin to the reactor and continue stirring for 0.5 hour; add coupling agent to the reactor and keep the temperature at 110°C, and continue stirring for a total of 2.5 hours; add hexamethylenetetramine to the reactor and continue stirring for 0.5 hour; add diisopropylbenzene peroxide to the reactor and continue stirring for 0.5 hour; add antioxidant to the reactor and continue stirring for 0.5 hour;
[0133] The pretreated barium sulfate, aluminum oxide, talcum powder, graphite, molybdenum disulfide, copper fiber, and silicon carbide particles are added to a high-speed mixer in proportion for heating and stirring. The heating temperature of the high-speed mixer is 80° C. The stirring and mixing time is 2.5 hours. A lubricant is added during the stirring and mixing process.
[0134] The mixed powder was added into the reactor and stirred for 0.5 hours, and then the pretreated high-strength carbon fiber, aramid fiber and basalt fiber were added into the mixed solution in the reactor and stirred, and ultrasonic dispersion was performed during stirring. The stirring time was 3.2 hours and the ultrasonic power was 1100W.
[0135] The stirred mixed material is poured into a mold and molded by injection molding. A magnetic field with a strength of 0.9T is applied to the mold by a magnetic field generating device. The temperature of injection molding is 205°C and the pressure is 85MPa.
[0136] The formed product is taken out of the mold and placed in an oven for curing. The temperature is gradually increased from room temperature to 205°C at a heating rate of 2.8°C / min. The curing time is 6.5 hours. During the curing process, the surface of the product is irradiated with ultraviolet light with a wavelength of 350nm and an irradiation intensity of 18mW / cm².
[0137] Example 8
[0138] The high friction coefficient organic track brake pad material is the same as that of Example 7;
[0139] The method for preparing the high friction coefficient organic rail brake pad material comprises:
[0140] The high-strength carbon fiber was soaked in potassium permanganate solution for 3.5 hours at a temperature of 55°C, and then the high-strength carbon fiber was rinsed with deionized water and then dried at 85°C for 4.5 hours; the aramid fiber treatment, basalt fiber treatment, filler treatment, resin mixing, and powder mixing were the same as in Example 7;
[0141] The mixed powder was added into the reactor and stirred for 0.5 hours, and then the pretreated high-strength carbon fiber, aramid fiber and basalt fiber were added into the mixed solution in the reactor and stirred, and ultrasonic dispersion was used during stirring. The stirring time was 2.8 hours and the ultrasonic power was 900W.
[0142] The stirred mixed material is poured into a mold and molded by injection molding. A magnetic field with a strength of 0.7T is applied to the mold by a magnetic field generating device. The injection molding temperature is 200°C and the pressure is 70MPa.
[0143] The formed product is taken out of the mold and placed in an oven for curing. The temperature is gradually increased from room temperature to 200°C at a heating rate of 2.3°C / min. The curing time is 6 hours. During the curing process, the surface of the product is irradiated with ultraviolet light with a wavelength of 300nm and an irradiation intensity of 16mW / cm².
[0144] Example 9
[0145] The high friction coefficient organic track brake pad material is the same as that of Example 7;
[0146] The method for preparing the high friction coefficient organic rail brake pad material comprises:
[0147] The high-strength carbon fiber was soaked in a nitric acid solution for 5 hours at a temperature of 70°C, and then the high-strength carbon fiber was rinsed with deionized water, and then dried at 100°C for 6 hours; the aramid fiber treatment, basalt fiber treatment, filler treatment, resin mixing, and powder mixing were the same as in Example 7;
[0148] The mixed powder was added into the reactor and stirred for 0.5 hours, and then the pretreated high-strength carbon fiber, aramid fiber and basalt fiber were added into the mixed solution in the reactor and stirred, and ultrasonic dispersion was used during stirring. The stirring time was 3.5 hours and the ultrasonic power was 1200W.
[0149] The stirred mixed material is poured into a mold and molded by injection molding. A magnetic field with a strength of 1T is applied to the mold by a magnetic field generating device. The temperature of injection molding is 210°C and the pressure is 90MPa.
[0150] The formed product is taken out of the mold and placed in an oven for curing. The temperature is gradually increased from room temperature to 210°C at a heating rate of 3°C / min. The curing time is 7 hours. During the curing process, the surface of the product is irradiated with ultraviolet light with a wavelength of 400nm and an irradiation intensity of 20mW / cm².
[0151] Comparative Example 1
[0152] Brake pad materials measured by mass percentage include:
[0153] Phenolic resin (general type) 70%, asbestos fiber 20%, copper powder 5%, graphite 5%.
[0154] The preparation method of the brake pad material comprises:
[0155] The asbestos fiber is dried at 100°C for 2 hours; the phenolic resin is added into a stirring kettle and stirred at 80°C, and then the dried asbestos fiber, copper powder and graphite are added in sequence and stirred for 2 hours to mix the components evenly; the mixed material is poured into a mold and pressed at 150°C and a pressure of 10MPa for 2 hours; the molded product is cured at 180°C for 4 hours.
[0156] Comparative Example 2
[0157] Brake pad materials measured by mass percentage include:
[0158] Nitrile rubber modified phenolic resin 60%, glass fiber 25%, molybdenum disulfide 8%, aluminum oxide 7%.
[0159] The preparation method of the brake pad material comprises:
[0160] The glass fiber was impregnated with a silane coupling agent (KH-550) for 1 hour and then dried at 120°C for 3 hours; the nitrile rubber modified phenolic resin was heated to 90°C in a reactor and stirred for 1 hour; molybdenum disulfide and aluminum oxide were mixed and added to the resin and stirred for 1.5 hours; the treated glass fiber was added to the mixture and stirred for 2 hours; hot pressing was used with a temperature of 170°C, a pressure of 15MPa, and a holding time of 2.5 hours; and curing was performed at 200°C for 5 hours.
[0161] Comparative Example 3
[0162] Brake pad materials measured by mass percentage include:
[0163] Epoxy resin 50%, steel fiber 20%, carbon powder 15%, calcium carbonate 15%.
[0164] The preparation method of the brake pad material comprises:
[0165] After cleaning the steel fiber with acetone, dry it at 80°C for 1.5 hours; stir the epoxy resin at 60°C, add carbon powder and calcium carbonate, stir for 1.5 hours, then add the steel fiber and continue stirring for 2 hours; use injection molding at a temperature of 180°C and a pressure of 50MPa; leave it at room temperature for 24 hours, and then cure it at 120°C for 3 hours.
[0166] The following is a comparison table of the performance parameters of the brake pad materials of Examples 1-9 and Comparative Examples 1-3:
[0167]
[0168] Through the above comparison, in terms of friction coefficient, the friction coefficient of Examples 1-9 is roughly between 0.41 and 0.47, which shows that the use of a specific high friction coefficient organic rail brake pad material formula and preparation process can stably obtain a higher friction coefficient. The materials in these embodiments contain a variety of functional components, such as lubricants and wear-resistant agents such as graphite and molybdenum disulfide. At the same time, the resin matrix such as thermosetting phenolic resin, bismaleimide resin, polyimide resin and the fiber reinforcement material work synergistically to ensure that friction can be effectively generated during braking. The friction coefficient of Comparative Examples 1-3 is significantly lower than that of the embodiments, between 0.3 and 0.35. The combination of traditional phenolic resin, asbestos fiber, copper powder and graphite in Comparative Example 1 has a friction performance that is not as good as the new material combination in the embodiments. The material systems in Comparative Examples 2 and 3, whether it is a combination of nitrile rubber modified phenolic resin and glass fiber, or a combination of epoxy resin and steel fiber, are inferior to the embodiments in terms of friction coefficient. This shows that the material formula and process in the embodiments have a significant effect on improving the friction coefficient.
[0169] In terms of wear rate, the wear rate of the embodiments is generally low, ranging from 0.022-0.027 mm³ / This is due to the use of fiber-reinforced materials such as high-strength carbon fiber, aramid fiber, basalt fiber, etc. in the material, which improves the strength and wear resistance of the material. At the same time, the fine processing and reasonable matching of various fillers, as well as complex preparation processes, such as fiber pretreatment, heating and stirring during powder mixing, ultrasonic dispersion, etc., all help to reduce the wear of the material during braking. The wear rate of the comparative example is relatively high, at 0.045-0.056mm³ / The asbestos fiber material in comparative example 1 has poor wear resistance, and the wear of the materials in comparative examples 2 and 3 during braking is not as good as that in the embodiment, which further highlights the advantages of the new materials and processes in the embodiments in reducing the wear rate.
[0170] In terms of compressive strength, the compressive strength of the embodiment is between 272-292 MPa. This is because the composite use of multiple high-performance resins provides good bonding properties for the material, firmly combining various reinforcing fibers and fillers. At the same time, fiber pretreatment and reasonable molding and curing processes, such as magnetic field action and ultraviolet irradiation, help to improve the structural stability inside the material, thereby enhancing the compressive strength. The compressive strength of the comparative example is significantly lower than that of the embodiment, between 180-205 MPa. The combination of general-purpose phenolic resin and asbestos fiber in comparative example 1 has limited compressive resistance. The material systems in comparative examples 2 and 3 cannot be compared with the embodiments in terms of compressive strength. This shows that the material and process design in the embodiments are more conducive to improving the compressive strength.
[0171] In terms of hardness, the hardness of the embodiment is between 211-225HB. The reasonable ratio of various reinforcing fibers and fillers in the material and the complex preparation process make the internal structure of the material dense, thereby improving the hardness. For example, pretreatment of the fiber can improve its bonding with the resin and improve the overall hardness of the material. The hardness of the comparative example is between 151-175HB, which is much lower than that of the embodiment. This shows that the material formula and preparation process in the embodiment have obvious advantages in improving hardness, and the traditional materials and simple processes in the comparative example cannot meet the requirements of high hardness.
[0172] It should be noted that the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, commodity or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, commodity or device. In the absence of further restrictions, the elements defined by the sentence "comprises a ..." do not exclude the existence of other identical elements in the process, method, commodity or device including the elements.
[0173] Each embodiment of the present invention is described in a progressive manner, and the same or similar parts between the embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. In particular, for the system embodiment, since it is basically similar to the method embodiment, the description is relatively simple, and the relevant parts can be referred to the partial description of the method embodiment.
[0174] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present disclosure is limited to these examples. Based on the concept of the present disclosure, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of different aspects of one or more embodiments of the present invention as described above, which are not provided in detail for the sake of simplicity.
[0175] While the disclosure has been described in conjunction with specific embodiments thereof, many alternatives, modifications and variations of these embodiments will be apparent to those skilled in the art in light of the foregoing description.
[0176] One or more embodiments of the present invention are intended to cover all such replacements, modifications and variations that fall within the scope of protection of the present invention. Therefore, any omissions, modifications, equivalent replacements, improvements, etc. made within the spirit and principles of one or more embodiments of the present invention should be included in the scope of protection of this disclosure.
Claims
1. A high friction coefficient organic rail brake pad material, characterized in that: The brake pad material comprises, by weight percentage, 20-30% thermosetting phenolic resin, 8-15% bismaleimide resin, 8-12% polyimide resin, 6-10% high-strength carbon fiber, 6-10% aramid fiber, 4-8% basalt fiber, 3-6% graphite, 2-5% molybdenum disulfide, 3-6% copper fiber, 2-5% silicon carbide particles, 3-6% barium sulfate, 2-4% aluminum oxide, 2-4% talcum powder, 2.5-5% curing agent and 1.5-3.5% other additives; The other additives include: 0.5-1.5% coupling agent, 0.5-1% lubricant and 0.5-1% antioxidant; the coupling agent includes at least one of γ-aminopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane and monoalkoxy titanate; the lubricant includes at least one of polyethylene wax, zinc stearate and polyethylene glycol; the antioxidant includes at least one of hindered phenol antioxidant, phosphite antioxidant and butylated hydroxytoluene.
2. The high friction coefficient organic rail brake pad material according to claim 1, characterized in that: The curing agent comprises: 1.5-3% of hexamethylenetetramine and 1-2% of dicumyl peroxide.
3. A method for preparing the high friction coefficient organic rail brake pad material according to claim 1 or 2, characterized in that: The preparation method comprises: S1: pretreating the high-strength carbon fiber, the aramid fiber, the basalt fiber, the barium sulfate, the aluminum oxide and the talc; S2: adding the thermosetting phenolic resin, the bismaleimide resin and the polyimide resin into a reaction kettle in proportion, heating and stirring, and then sequentially adding a coupling agent, a curing agent and an antioxidant into the reaction kettle and continuing stirring; S3: adding the pretreated barium sulfate, aluminum oxide, talcum powder, graphite, molybdenum disulfide, copper fiber, and silicon carbide particles into a high-speed mixer in proportion, heating and stirring, and adding a lubricant during the stirring and mixing process; S4: adding the mixed powder into a reactor and stirring, and then adding the pretreated high-strength carbon fiber, the aramid fiber, and the basalt fiber into the mixed liquid in the reactor and stirring; S5: pouring the mixed material stirred in step S4 into a mold and molding it by injection molding; S6: taking the formed product out of the mold and putting it into an oven for curing; S7: Perform mechanical processing, surface treatment and heat treatment on the cured product.
4. The method for preparing the high friction coefficient organic rail brake pad material according to claim 3, characterized in that: Step S1 specifically includes: S11: soaking the high-strength carbon fiber in nitric acid or potassium permanganate solution for 3-5 hours at a temperature of 50-70° C., then rinsing the high-strength carbon fiber with deionized water, and then drying the high-strength carbon fiber at 80-100° C. for 4-6 hours; S12: impregnating the aramid fiber with a mixed solution of a silane coupling agent and a titanate coupling agent in a mass ratio of 1:1 for 2-4 hours at a temperature of 60-80° C., then rinsing the aramid fiber with deionized water, and drying the aramid fiber at 100-120° C. for 3-5 hours; S13: using a plasma treatment device to perform surface plasma treatment on the basalt fiber, the treatment time is 1-2 hours, and the power is 500-1000W; S14: drying the barium sulfate, the aluminum oxide and the talc powder respectively at a drying temperature of 120-150° C. for 5-8 hours, and then grinding the barium sulfate, the aluminum oxide and the talc powder respectively to make the particle sizes of the barium sulfate, the aluminum oxide and the talc powder be 1-5 μm.
5. The method for preparing the high friction coefficient organic rail brake pad material according to claim 3, characterized in that: Step S2 specifically includes: S21: adding the thermosetting phenolic resin into a reaction kettle, and stirring at 90-110° C. for 0.5 hour; S22: Add the bismaleimide resin into the reaction kettle and continue stirring for 0.5 hours; S23: Add the polyimide resin into the reaction kettle and continue stirring for 0.5 hours; S24: Add coupling agent to the reaction kettle and maintain the temperature at 90-110° C., and continue stirring for a total of 1.5-2.5 hours; S25: adding hexamethylenetetramine to the reaction kettle and continuing stirring for 0.25-0.5 hours; S26: Add dicumyl peroxide to the reactor and continue stirring for 0.25-0.5 hours; S27: Add antioxidant to the reactor and continue stirring for 0.3-0.5 hours.
6. The method for preparing the high friction coefficient organic rail brake pad material according to claim 3, characterized in that: In step S3, the heating temperature of the high-speed mixer is 60-80° C., and the stirring and mixing time is 1.5-2.5 hours; and / or, In step S4, the mixed powder is added to a reactor and stirred for 0.5 hours, and the pretreated high-strength carbon fiber, the aramid fiber, and the basalt fiber are added to the mixed liquid in the reactor and stirred. Ultrasonic dispersion is performed during stirring. The stirring time is 2.5-3.5 hours, and the ultrasonic power is 800-1200W.
7. The method for preparing the high friction coefficient organic rail brake pad material according to claim 3, characterized in that: During the injection molding process of step S5, a magnetic field with a strength of 0.5-1T is applied to the mold by a magnetic field generating device; and / or, In step S5, the injection molding temperature is 190-210°C and the pressure is 60-90 MPa.
8. The method for preparing the high friction coefficient organic rail brake pad material according to claim 3, characterized in that: In step S6, the oven is heated from room temperature to 190-210°C at a heating rate of 2-3°C / min, and the curing time is 5-7 hours; and / or, During the curing process of the product, ultraviolet light is used to irradiate the surface of the product. The wavelength of ultraviolet light is 200-400nm and the irradiation intensity is 10-20mW / cm².
Citation Information
Patent Citations
Carbon fiber reinforced friction-resistant polyoxymethylene (POM) composite material and preparation method thereof
CN104356589A
Manufacturing method of high-performance environment-friendly automobile brake pad
CN104405807A
Friction plate material and preparation method therefor
CN106190024A